APLIKASI TMS (TICKET MONITORING SYSTEM) SAFARI DHARMA RAYA DENGAN JSP (Information Technology and Telematics, 2014)
Abstract :Safari Dharma Raya is a company engaged in Waterford City transport bus transport services that serve evening. A large number of fleet and bus lines on the PO. Safari Dharma Raya makes this company representatives put agents in every city that became the bus lines. The number of agents that are spread in the Java-Bali has reached tens. At this time, ticket sales transactions and accounting is done manually, this makes the company less than optimal performance. So the need for ticket sales system that can bridge this problem.This study aims to design a monitoring application and a bus ticket booking PO. Safari Dharma Raya. By using a computer connected to the Internet connection can be used to access the system based on client's server. Settings page of the website is done using JSP programming language.The system is designed in such a way to allow users to perform a bus ticket reservation. In addition, reports can be accumulated each day is helpful performance officer at the center can check pambukuan every week.Keywords: Ticket Monitoring System, Java Server Pages